Pengenalan dan Pemanfaatan Marketplace Shopee Untuk Meningkatkan Penjualan UMKM Kelurahan Sananwetan Kota Blitar - Wahyu Nurbayzura; Tuhfatul Ahbab; Nafisa Dean Putri Aqila; Intan Sulistyowati; Gagas Pandu Khrisna; Mentari Clara Dewanti; Ira Wikartika; Siti Aminah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The development of information technology today is very sophisticated and rapid. The development of the internet in Indonesia is also increasing. Based on the survey results of the Indonesian Internet Service Providers Association (APJII), there are 210.03 million internet users in the country in the period 2021-2022. The service activity carried out by the 143 KKN-T MBKM UPN "Veteran" East Java group was aimed at Micro, Small and Medium Enterprises (MSMEs) in the Sananwetan village. The purpose of this study is to introduce and explain the benefits of the Shopee marketplace to increase sales of Micro, Small and Medium Enterprises (MSMEs) in the Sananwetan village. Marketplace is an internet-based online media (web-based) where business activities and transactions are carried out between buyers and sellers. Buyers can find as many suppliers as possible with the desired criteria, so they get the right price. Shopee was chosen for MSMEs because the platform is tailored for each region and provides an easy, safe and fast online shopping experience for customers through strong payment and logistics support.